Respuesta :

Answer:

11. [tex]4x^{3}-10x^{2}+6x[/tex]

Take out 2x ( greatest common factor )
[tex]2x(2x^{2}-5x+3)[/tex]

Factor

[tex]2x(2x^{2} -2x-3x+3)[/tex]

[tex]2x(x-1)-3(x-1)=(2x-3)(x-1)[/tex]

Don't forget about the 2x we took out earlier

Solution to 11: [tex]2x(2x-3)(x-1)[/tex]

12. [tex]16x^{2} -25y^{2}[/tex]

This is the difference of squares, so let's use the formula...

[tex]a^{2}-b^{2}=(a-b)(a+b)[/tex]

if, [tex]a=16x^{2}[/tex] and [tex]b=25y^{2}[/tex]

then, the Solution to 12 is:

[tex](4x-5y)(4x+5y)[/tex]

13. [tex]3x^3-24[/tex]

First of all, you must find the greatest common factor because there isn't anything else you can do.

[tex]3(x^3-8)[/tex]

Now you can see the difference of cubes...

[tex]a^3-b^3=(a-b)(a^2+ab+b^2)[/tex]

so, the Solution to 13 is:

[tex]3(x^3-8)= 3(x-2)(x^2+2x+4)[/tex]